A model to investigate the effect of information technology and information systems on the ease of managers' decision-making. Issue 1 (17th March 2020) - Ming, Tian; Teng, Wang; Jodaki, Susan
Abstract : Purpose: Decision-making and problem-solving are ongoing progressions of evaluating situations or problems, considering substitutes, making choices and following them up with the necessary actions. The relationship between managers' decision-making and information technology (IT) has long been of interest to researchers. This study aims to examine the changes in novel technologies in facilitating managers' decisions that influence the quality and timeliness of information and decision-making. Design/methodology/approach: The present paper is a descriptive-correlative study in terms of the data collection method and is applicable in terms of purpose. In addition, the library-field method was used to collect information. Because of the target and subject of the research of the statistical population, this research contains all managers of a management organization that are 100 people. The present study is used in the structural equation modeling method to examine causal models and evaluate the reliability and validity of the measurement model. The presented model and the gathered information from the questionnaires were analyzed through SmartPLS software. Findings: The results indicate that the IT infrastructure, expert systems, marketing information systems (ISs) and organizational variables significantly influence the ease of managers' decision-making and considering these dimensions is a step in the success of managers' decisions. Research limitations/implications: This study used a questionnaire to collect information, which may result in some people refusing to provide a real answer and giving an unrealistic answer. This study is also cross-sectional, and therefore, makes it difficult to conclude about causality. In addition, access to statistics and information is one of the significant pillars of research. Practical implications: The paper presents useful advice for improving decision-making. In addition, the topic is relevant to the ease of managers' decisions. A better understanding of the impact of IT infrastructure, expert systems, marketing ISs and organizational variables could significantly enhance managers' success. Originality/value: The ideas and topics discussed are equally applicable to libraries and can provide new insights into the impact of IT infrastructures, expert systems, marketing ISs and organizational variables on the ease of decision makers as a source of competition.